Penerapan Teknik Ecoprint Untuk Meningkatkan Motorik Halus Anak Usia Dini - Mutiara Ramadhanni; Asnawati Asnawati; Rika Partika Sari (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This study was initiated by the low level of fine motor skills among early childhood students at Lembayung Indah Kindergarten in Bengkulu City, which stemmed from a lack of variation in learning methods and insufficient stimulation through engaging activities. Drawing upon Hurlock’s theory of fine motor development and the constructivist approach, hands-on experiential activities such as ecoprinting are believed to enhance children's hand-eye coordination. This study aims to examine the implementation of the ecoprint technique in improving the fine motor skills of children aged 5–6 years. The method employed was Classroom Action Research (CAR) following the Kemmis and McTaggart model, conducted across two cycles, each consisting of planning, acting, observing, and reflecting. Data collection techniques included observation, documentation, and performance assessment, with data analyzed using percentage analysis. The results demonstrated a significant improvement in each cycle: increasing from 36% in Cycle I Session I to 51%, then rising to 73% in Cycle II Session I, and ultimately reaching 91% in Cycle II Session II, falling into the